Physical and mental health factors associated with work engagement among Finnish female municipal employees: A cross-sectional study - Veromaa V.; Kautiainen H.; Korhonen P. (BMJ Publishing Group, 2022)
Objectives: Work engagement is related to mental health, but studies of physical health’s association with work engagement are scarce. This study aims to evaluate the relationship between physical health, psychosocial risk factors and work engagement among Finnish women in municipal work units.
Methods: A cross-sectional study was conducted in 2014 among 726 female employees from 10 municipal work units of the city of Pori, Finland. Work engagement was assessed with the nine-item Utrecht Work Engagement Scale. The American Heart Association’s concept of ideal cardiovascular health (CVH) was used to define physical health (non-smoking, body mass index <25.0 kg/m2, physical activity at goal, healthy diet, total cholesterol <5.18mmol/L, blood pressure <120/80 mm Hg, normal glucose tolerance). Psychosocial risk factors (social isolation, stress, depressive symptoms, anxiety, hostility and type D personality) were included as core questions suggested by 2012 European Guidelines on cardiovascular disease prevention.
Results: Of the study subjects, 25.2% had favourable 5–7 CVH metrics. The sum of CVH metrics, healthy diet and physical activity at goal were positively associated with work engagement. In subjects without psychosocial risk factors (36.7%), work engagement was high and stable. Presence of even one psychosocial risk factor was associated with a lower level of work engagement regardless of the sum of ideal CVH metrics.
Conclusions: Both physical and mental health factors have a positive relationship with work engagement, whereas the presence of even one psychosocial risk factor has a negative association regardless of the level of classic cardiovascular risk factors.